ORIGINAL PAPERThe lipid disorders therapy in overweight patients - Rysz, Jacek; Banach, Maciej; Stolarek, Robert; Irzmański, Robert; Markuszewski, Leszek; Wilk, Radosław (Archives of Medical Science, 2005)
Introduction: The study was aimed to assess effects of hypercholesterolemia and the dyslipidemia therapy within one year of recommended lifestyle and diet modifications. Material and methods: The study included 157 consecutive patients referred to the Outpatient Department of Metabolic Disorders with hypercholesterolemia diagnosis. Patients were assigned based on body weight and BMI into three groups: 1) patients with normal body weight (BMI 18.5 25-30) and 3) obese patients (BMI >30). The therapeutical effects were studied 6 and 12 months after the initiated therapy. The degree of body weight reduction, incidence and time frame of normal lipid panel, incidence and time of drop-outs in relation to the remaining IND and CVI risk factors were studied. Results: Total cholesterol was significantly increased before the study in overweight patients. After 6 months, the percentage of patients who reached the therapeutical targets was 30.56% in obese patients, 35.29% in overweight patients, and 29.41% in patients with normal body weight. After 12 months, the highest percentage of patients reaching therapeutical targets was 47.06% in the group with normal body weight. Conclusions: 1. Time frame and incidence of successful therapy and eventual, normal lipids panel is remarkably related with initial body weight. 2. Subjects with normal body weight benefited from the 12 months therapy to the largest extent. 3. Overweight and obese patients are less motivated to diet and lifestyle changes resulting in the highest number of patients with increased body weight during the dyslipidemia therapy.